2011
DOI: 10.4103/0970-0218.84135
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practices about biomedical waste management among healthcare personnel: A cross-sectional study

Abstract: Background:The waste produced in the course of healthcare activities carries a higher potential for infection and injury than any other type of waste. Inadequate and inappropriate knowledge of handling of healthcare waste may have serious health consequences and a significant impact on the environment as well.Objective:The objective was to assess knowledge, attitude, and practices of doctors, nurses, laboratory technicians, and sanitary staff regarding biomedical waste management.Materials and Methods:This was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
129
5
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(195 citation statements)
references
References 4 publications
35
129
5
8
Order By: Relevance
“…As similar to study conducted by Mathur et al; 6 the present study revealed that more than 90% of medical officers had knowledge about biomedical waste management guidelines and segregation with lesser knowledge among staff nurses (55.0%) and paramedical staff (62.5%) and least awareness among class IV workers. Similar findings were also reported in other studies.…”
Section: Discussionsupporting
confidence: 74%
“…As similar to study conducted by Mathur et al; 6 the present study revealed that more than 90% of medical officers had knowledge about biomedical waste management guidelines and segregation with lesser knowledge among staff nurses (55.0%) and paramedical staff (62.5%) and least awareness among class IV workers. Similar findings were also reported in other studies.…”
Section: Discussionsupporting
confidence: 74%
“…This is much higher than what was About 86% of students in our study knew about the categories of dental waste materials generated in the clinics, which is similar to the study by reported by Sanjeev et al [8] (96.6%), Chudasama et al [10] (96.5%), Manchanda et al [11] (90%), and Mathur et al [9] (81.3%). However, in the study by Bansal et al [7], only 76% of the dentists segregated different wastes according to the laws of BMW management.…”
Section: Discussionsupporting
confidence: 70%
“…This shows that our study participants have excellent knowledge and practices regarding discarding needles. This was much higher than the results observed by Mathur et al [9], Bansal et al [7], and Chudasama et al [10] where only around 65.3%, 58%, and 63.1% used to dispose sharps in puncture-proof containers. Whereas only 41.7% and 26.4% of study participants disposed needles in puncture proof containers according to the study by Manchanda et al [11] and Charania and Ingle [5], respectively.…”
Section: Discussioncontrasting
confidence: 55%
“…The waste produced in the course of healthcare activities carries a higher potential for infection and injury than any other type of waste. 1 Bio-medical waste (BMW) is defined as "any waste which is generated during the diagnosis, treatment or immunization of human beings or animals or in research activities pertaining thereto or in the production or testing of biologicals".…”
Section: Introductionmentioning
confidence: 99%